Bio‐electrochemical response to sense implant degradation. Issue 6 (19th May 2020) - Shittu, Jibril; Sadeghilaridjani, Maryam; Pole, Mayur; Ayyagari, Aditya; Mukherjee, Sundeep
Abstract: In vivo monitoring of biomedical implants to detect early stages of failure is currently unavailable. State‐of‐the‐art imaging techniques do not provide information about small‐scale localized changes in the implant and surrounding environment, which are key to early detection of failure. Here, we discuss different electrochemical responses of implants during degradation which may be utilized to develop biosensors to monitor implant degradation in vivo. This review is focused on identifying the need, potential measurement techniques and degradation response obtained from sensors based on electrochemical signature of biomedical implants. Benefits of designing these novel sensors include continuous monitoring, early failure detection, reduced post‐surgery and prevention of catastrophic failure from implant degradation.